GLI1-expressing mesenchymal cells form the essential Wnt-secreting niche for colon stem cells - Degirmenci, Bahar; Valenta, Tomas; Dimitrieva, Slavica; Hausmann, George; Basler, Konrad (Nature, 2018)
Wnt-β-catenin signalling plays a pivotal role in the homeostasis of the intestinal epithelium by promoting stem cell renewal1,2. In the small intestine, epithelial Paneth cells secrete Wnt ligands and thus adopt the function of the stem cell niche to maintain epithelial homeostasis3,4. It is unclear which cells comprise the stem cell niche in the colon. Here we show that subepithelial mesenchymal GLI1-expressing cells form this essential niche. Blocking Wnt secretion from GLI1-expressing cells prevents colonic stem cell renewal in mice: the stem cells are lost and, as a consequence, the integrity of the colonic epithelium is corrupted, leading to death. GLI1-expressing cells also play an important role in the maintenance of the small intestine, where they serve as a reserve Wnt source that becomes critical when Wnt secretion from epithelial cells is prevented. Our data suggest a mechanism by which the stem cell niche is adjusted to meet the needs of the intestine via adaptive changes in the number of mesenchymal GLI1-expressing cells.
Keywords: kolon; Male; Wnt Signaling Pathway; Intestine, Small; mužské pohlaví; proteiny Wnt; buněčná sebeobnova; Wnt Proteins; Stem Cells; Animals; ženské pohlaví; nika kmenových buněk; zvířata; Colon; myši; tenké střevo; Zinc Finger Protein GLI1; protein Gli1; Mice; signální dráha Wnt; Female; Stem Cell Niche; Mesenchymal Stem Cells; kmenové buňky; Cell Self Renewal; mezenchymální kmenové buňky